2010
DOI: 10.1348/096317909x477495
|View full text |Cite
|
Sign up to set email alerts
|

Does serving the community also serve the company? Using organizational identification and social exchange theories to understand employee responses to a volunteerism programme

Abstract: Little is known about how employees might respond to their company's socially responsible business practices. Hypotheses derived from organizational identification and social exchange theories were tested to explain why employees (N=162) may respond positively to their company's volunteerism programme, a programme through which employees could spend time volunteering during their paid work hours. Support was found for mediated effects suggesting that employees' attitude towards the volunteerism programme ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
550
1
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(584 citation statements)
references
References 47 publications
19
550
1
14
Order By: Relevance
“…More widely, it has been noted that participating in voluntary work is associated with positive feelings for volunteers (Post, 2005), and Tidwell (2005) showed that volunteers who identify with their voluntary employer's vision and values are more satisfied and committed with their volunteering work. These findings resonate with studies on corporate sponsored volunteering, which demonstrate that volunteer involvement leads to beneficial outcomes for the volunteers, the voluntary organization, and the employer who sponsored the volunteering activities (e.g., Booth et al, 2009;Jones, 2010;Rodell, 2013). For example, Caliguri et al (2013) showed that volunteering assignments which included meaningful projects, social support within the voluntary organization, and opportunities for skill development yielded positive benefits for the employer (i.e.…”
Section: Outcomes Of Volunteer Engagementsupporting
confidence: 63%
See 1 more Smart Citation
“…More widely, it has been noted that participating in voluntary work is associated with positive feelings for volunteers (Post, 2005), and Tidwell (2005) showed that volunteers who identify with their voluntary employer's vision and values are more satisfied and committed with their volunteering work. These findings resonate with studies on corporate sponsored volunteering, which demonstrate that volunteer involvement leads to beneficial outcomes for the volunteers, the voluntary organization, and the employer who sponsored the volunteering activities (e.g., Booth et al, 2009;Jones, 2010;Rodell, 2013). For example, Caliguri et al (2013) showed that volunteering assignments which included meaningful projects, social support within the voluntary organization, and opportunities for skill development yielded positive benefits for the employer (i.e.…”
Section: Outcomes Of Volunteer Engagementsupporting
confidence: 63%
“…Previous research has suggested that organizations can foster volunteering by offering employees the opportunity to participate in volunteering activities (e.g., Booth et al, 2009;Caligiuri, Mencin, & Jiang, 2013;Grant, 2012;Jones, 2010;Rodell, 2013). This is usually done as part of corporate volunteerism programs where employers sponsor release time and regular compensation to enable interested employees to donate their time to a specific cause.…”
mentioning
confidence: 99%
“…Individual factors which have been studied include attitudes and beliefs (Jones, 2010;Chun, Shin, Choi & Kim, 2013;Manika, Wells, Gregory-Smith & Gentry, 2014), norms (Scherbaum, Popovich & Finlinson, 2008;Carrico & Riemer, 2011), self-efficacy (Smith & O'Sullivan, 2012), habit (Siero et al, 1996), motivation (Lee, De Young & Marans, 1995;Tudor, Barr & Gilg, 2008), knowledge (Siero et al, 1984) and socio-demographics (Wehrmeyer & McNeil, 2000). The most comprehensive study of employee environmental behaviour within the tourism literature focused on individual (individual environmental beliefs, personal environmental norms, self-reported environmental behaviour) and organisational variables (green organisational climate) as well as demographics to explain employee behaviour (Chou, 2014).…”
Section: Employee Environmental Behaviourmentioning
confidence: 99%
“…Research has unveiled a positive relationship between corporate social responsibility and workers' commitment to the companies they work for (Brammer, Pavelin, & Porter, 2009), either through the strengthening of the emotional ties they have to these organizations, or through an increased sense of duty and obligation to their companies (Eisenberg, Kilduff, Burleigh, & Wilson, 2001). Other studies have shown that when employees believe that the company which they work for is committed to them, guaranteeing their rights as workers, protecting their health and safety and investing in their professional development, their emotional ties and desire to remain at this company are positively influenced (Brammer, Millington, & Rayton, 2007;Jones, 2010).…”
Section: Hypothesesmentioning
confidence: 99%